Impact of the Family Structure on Satisfaction with Household Income in Urban Peru - Riesco Lind, Gustavo (2015)
Family structure affects not only household income but can influence how revenues contributeto financial satisfaction. That is to say, it is possible that a certain family structure can be more efficient in producing satisfaction than another. Using microdata from the National Household Survey (ENAHO) 2013, a probit econometric model is proposed for urban households in Peru, in which the likelihood of satisfaction with household income is a function of income itself, both in absolute terms and relative to other households, and of various household characteristics, including aspects of family structure. Analysis of ENAHO 2013 reveals that 80.2% of house- holds report being satisfied with their income; satisfaction levels among lone parents are the lower than in other groups (77.3%) and the highest satisfaction levels are reported by married couples with children and cohabiting couples with children (82.8% and 80.3% respectively). Results of the regression model support the conclusions of other studies, in that per capita hou- sehold income has a positive impact on the probability of income satisfaction; however, it is not the only significant variable. In particular, we have found evidence that the difference between household expenditure and average household expenditure in the region (a measure of relative expenditure) also influences the likelihood of income satisfaction, as well as changes in household economy relative to that of other households in the area. Regarding family structures considered in the study, households of married couples with children, cohabiting couples with children, and cohabiting couples without children are less responsive than other households in several variables: number of household members, income per capita, difference between household expenditure and the regional average, and university education of the household head. In single- parent households in general, satisfaction with income is particularly sensitive to changes in the number of household members, per capita income, difference between household expenditure and the regional average, university education of the household head, and perception of declinein household living standards relative to other households in the area.